International financial institutions and the provision of international goods - Joseph E. Stiglitz (EIB Papers, 1998)
Changes in the role of collective action at the international level, in the international economic environment, and, most importantly, our better understanding of economics in general require that we rethink the role of international financial institutions (IFIs). For multilateral development banks like the World Bank, their central mission, the promotion of growth and the reduction of poverty, is clear. The steps toward fulfilling this mission in a changing world are also relatively clear, and many of these institutions have already begun processes of renewal. But all of the IFIs have, in one way or another, also been involved in crisis management, especially in recent years. Here, future roles are less clear because they depend on the redefinition of the international financial architecture - a redefinition that has been hotly debated, but has not yet crystallised into a shared vision. The theoretical underpinnings - as well as the practical implementation - of alternative visions will require far more development before clarity on a future role will be attained. In this essay, I will address these questions from the perspective of the theory of international public goods, which is a powerful way to organise our thinking both on why we have IFIs in the first place, and the role that they should play in a changing world.
Keywords: 330; Entwicklungsbank; Entwicklungsorganisation; Internationaler Finanzmarkt; Öffentliches Gut; Welt; Theorie